The psychological aspect of the Holy Prophet (PBUH)'s strategy on the military front: عسکری محاذ پر رسول اللہ ﷺ کی حکمتِ عملی کا نفسیاتی پہلو - Rahim, Asma; Muhammad, Dr. Taj (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
To ensure national security, state's defense, and the establishment of peace and stability, the need for the army and military institutions has been inevitable at all times. For the Islamic state, a strong defense institution and its army are not just a manifestation of strength and power but also an important requirement for the protection of Islam and its survival. After the establishment of the Islamic state in Medina, the Holy Prophet (PBUH) began Jihad in obedience of God's command to avoid the evil incitement and oppression of enemies of Islam. He (PBUH) took possible steps to build a strong military system and through his extraordinary military strategy, understanding and insight, he (PBUH)defeated great enemy army many times. He (PBUH) was deeply familiar with the human psychology. As a commander he (PBUH) made brilliant and effective use of military psychological strategies and tactics. On the one hand, he (PBUH) kept the morale of his troops high through enthusiasm and positive narratives and gave them the assurance of Divine pleasure and victory. And on the other hand with great psychological steps he (PBUH) created an atmosphere of fear, despair and uncertainty for opponents. Along with establishing terror and awe, he (PBUH) also gained psychological superiority over his enemies by winning their hearts through kindness. He (PBUH) set an example to the world that war is not fought solely through weapons but through effective military psychological strategy which prevents the loss of weapons and human lives and repels the enemy on the mental and moral front.